2013
DOI: 10.1136/bjsports-2012-091788
|View full text |Cite
|
Sign up to set email alerts
|

Exercise during pregnancy and gestational diabetes-related adverse effects: a randomised controlled trial

Abstract: Regular moderate-intensity exercise performed over the second-third trimesters of pregnancy can be used to attenuate important GDM-related adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
219
0
33

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(258 citation statements)
references
References 45 publications
6
219
0
33
Order By: Relevance
“…[28][29][30][31][32][33][34][35][36][37][38] Reasons for refusal to provide IPD included lack of time, 39,40 problems with data sharing 41 and conflicts of interest. 42,43 Data were lost in two trials. 44,45 Sixteen randomised controlled trials (RCTs) (including 2265 women) were identified too late in the project to be analysed, and thus we refrained from approaching the authors.…”
Section: Network Meta-analysismentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37][38] Reasons for refusal to provide IPD included lack of time, 39,40 problems with data sharing 41 and conflicts of interest. 42,43 Data were lost in two trials. 44,45 Sixteen randomised controlled trials (RCTs) (including 2265 women) were identified too late in the project to be analysed, and thus we refrained from approaching the authors.…”
Section: Network Meta-analysismentioning
confidence: 99%
“…Seven randomized controlled trials, published between 2009 and 2012, are summarized in Table 1 [32][33][34][35][36][37][38]. In contrast to observational data, a recent summary of five of these studies concluded that they could find no clear effect on preventing GDM [39].…”
Section: Can Exercise Prevent Gdm?mentioning
confidence: 99%
“…Regular exercise in pregnancy has been shown to be protective against the development of pre-eclampsia in non diabetic pregnancies [58], and may provide similar protection for women with GDM. In addition, a recently published study examining the role of moderate-intensity exercise in reducing the comorbidities of GDM has reported a one-third reduction in the risk of undergoing acute or elective cesarean delivery for women who developed GDM (exercise OR: 1.30; 95% CI: 0.44-3.84 vs control OR: 1.99; 95% CI: 0.98-4.06) [38]. Taken together, these findings suggest that regular prenatal exercise may reduce the risk of pregnancy complications in women with GDM [59].…”
Section: Short-and Long-term Maternal Health Consequences Of Gdmmentioning
confidence: 99%
See 2 more Smart Citations